Studi Kritik Hadis tentang Keutamaan Shalat Berjamaah - Fitriana Aswati; Teti Ratnasih; Dian Siti Nurjanah (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about the primacy of prayer according to the hadith. This study uses a qualitative approach with a descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the primacy of praying in congregation in the hadith narrated by Bukhari no. 610. The results and discussion of this study indicate that the quality of the hadith is considered authentic with the qualification of maqbul ma'mul bih for the practice of Islam regarding congregational prayers that are full of virtues. This study concludes that the hadith narrated by Bukhari no. Relevant 610 is used as an argument for Muslim parents to cultivate their children's interest in performing congregational prayers so that a strong character foundation is formed when they are faced with busyness due to the times.